Scaffolding English Learning for Non-Native Speakers: A TEFL Approach in Multilingual Context - Sylvia Irene Persulessy; Juvrianto Chrissunday Jakob; Hien Pham; Mohammed H. Alaqad; Andi Asrifan (IJECA (International Journal of Education and Curriculum Application), 2026)
In multilingual settings like Indonesia, English language instruction encounters considerable obstacles stemming from learners' different linguistic backgrounds and differing competence levels. Despite scaffolding being acknowledged as a successful method in Teaching English as a Foreign Language (TEFL), its empirical implementation in multilingual Indonesian classrooms is still inadequately investigated. This study examines the impact of scaffolded instruction on English language competency, student engagement, and confidence in non-native secondary school learners. The study utilized a mixed-method explanatory sequential design, involving 60 students and 4 teachers, and incorporated language competence assessments, questionnaires, classroom observations, and semi-structured interviews. Quantitative data were studied by descriptive and inferential statistics, and qualitative data were assessed thematically. The results indicate that the experimental group exhibited a considerable enhancement, increasing from a pre-test mean score of 68 to 84 in the post-test (p < 0.01), surpassing the control group. Students indicated elevated motivation (M = 4.6) and perceived utility of scaffolding (M = 4.7). Observational and interview data reveal enhanced involvement, confidence, and culturally appropriate pedagogical approaches. These findings underscore the efficacy of context-sensitive scaffolding in improving both cognitive and emotional aspects of language acquisition. The study enhances TEFL research by supplying actual information from multilingual classrooms and presents practical suggestions for developing inclusive and flexible instructional practices.